2009
DOI: 10.1002/cphc.200900054
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Excitation Scavenging in Films of Conjugated Polymers

Abstract: Phosphorescence and delayed fluorescence of polyfluorene polymer films doped with cyclooctatetraene (COT) and anthracene are studied by means of time-resolved photoluminescence (PL) measurements. The occurrence of an anomalous nonvertical triplet energy transfer in solid conjugated polymer films is demonstrated for the first time employing the "nonvertical" COT triplet acceptor, which appears to behave similarly to conventional vertical triplet acceptors, such as anthracene. Both dopant molecules are found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…100 fs, which relies on chromophore interactions . Efforts to avoid a slow ISC process and control the formation of triplets have been suggested by either utilizing the intermittent excitation methods in engineering (replenishing dye fluids, pulse photoexcitation, or spinning micro‐disk) or using a blend of fluorophores and scavengers that could partially quench the triplets . However, the residual triplet states retain significant losses and are hitherto the major problem in evolving organic optics, for instance, in developing compact organic optical devices.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…100 fs, which relies on chromophore interactions . Efforts to avoid a slow ISC process and control the formation of triplets have been suggested by either utilizing the intermittent excitation methods in engineering (replenishing dye fluids, pulse photoexcitation, or spinning micro‐disk) or using a blend of fluorophores and scavengers that could partially quench the triplets . However, the residual triplet states retain significant losses and are hitherto the major problem in evolving organic optics, for instance, in developing compact organic optical devices.…”
Section: Figurementioning
confidence: 99%
“…[9] Efforts to avoid aslow ISC process and control the formation of triplets have been suggested by either utilizing the intermittent excitation methods in engineering (replenishing dye fluids, pulse photoexcitation, or spinning micro-disk) [10,11] or using ab lend of fluorophores and scavengers that could partially quench the triplets. [12,13] However,t he residual triplet states retain significant losses and are hitherto the major problem in evolving organic optics,f or instance,i nd eveloping compact organic optical devices.H erein, we report an innovative synthetic approach where high-energy-gap molecular barriers are intercalated in ap eriodic p-conjugated molecular array ( Figure 1A), which effectively cut off the interaction of the low-energy-gap fluorophores,r esulting in the absence of triplet states.…”
mentioning
confidence: 99%
“…To date, there have been so far only demonstrations of quasi-cw operation in DFB lasers based on a modified PFO derivative containing 12% of statistical 6,6-(2,2 0 -octyloxy-1,1 0 -binaphthalene) binaphthyl interchain spacer groups. When pumped at a very low duty cycle (<0.1%) with pulses of 400 μm duration these sources generated sequences of laser pulses with repetition rates up to 5 MHz [191,192]. Triplet "scavengers", which are routinely used to address the problem of triplet absorption in liquidstate dye lasers, have been tested as a possible solution to the same problem in conjugated polymers [193].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…[11][12][13][14][15][16] These absorption loss and emission quenching are signifi cant issues that must be solved to achieve cw and quasi-cw operation because they cause the lasing threshold to dramatically increase and, in the worst case, stop the lasing completely. [17][18][19] To suppress the absorption loss and emission quenching, the incorporation of triplet quenchers, such as oxygen, [ 15,16 ] cyclooctatetraene, [ 20 ] or an anthracene derivative, [ 19 ] in organic fi lms has been proposed. However, as suggested by Schols et al, [ 20 ] the requirements of triplet quenchers are a low triplet energy, a short triplet lifetime, and a large difference between the energies of the singlet and triplet states, making it diffi cult to discover suitable triplet quenchers that satisfy these conditions without impeding lasing.…”
mentioning
confidence: 99%
“…[17][18][19] To suppress the absorption loss and emission quenching, the incorporation of triplet quenchers, such as oxygen, [ 15,16 ] cyclooctatetraene, [ 20 ] or an anthracene derivative, [ 19 ] in organic fi lms has been proposed. However, as suggested by Schols et al, [ 20 ] the requirements of triplet quenchers are a low triplet energy, a short triplet lifetime, and a large difference between the energies of the singlet and triplet states, making it diffi cult to discover suitable triplet quenchers that satisfy these conditions without impeding lasing. Rabe et al demonstrated quasi-cw operation at a repetition rate of 5 MHz in a poly(9,9-dioctylfl uorene) derivative containing 6,6′-(2,2′-octyloxy-1,1′-binaphthalene)binaphthyl spacer groups of 12% (BN-PFO) without triplet quenchers.…”
mentioning
confidence: 99%